Composite semipermeable membrane, composite semipermeable membrane assembly and fluid separation device
By introducing a cross-linked polyamide separation functional layer and a vinyl alcohol or alkylene glycol polymer coating layer into the composite semipermeable membrane, the surface properties and structural shape are controlled, the problem of reduced separation performance caused by friction is solved, and both friction resistance and water permeability are achieved.
Patent Information
- Application Number
- CN202480009955.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-03
- Filing Date
- 2024-02-01
- Publication Date
- 2025-09-05
- Estimated Expiration
- 2044-02-01
AI Technical Summary
The existing composite semipermeable membranes are prone to degradation of separation performance during the friction process, and it is difficult to achieve both water permeability and friction resistance.
A separation functional layer comprising a cross-linked polyamide and a coating layer comprising a vinyl alcohol or alkylene glycol polymer is used, the expanded area ratio and friction coefficient of the side surface of the coating layer are controlled, and a pleated shape structure is formed to enhance friction resistance while maintaining good water permeability.
The composite semipermeable membrane maintains excellent friction resistance and water permeability during the friction process, thereby improving the service life and separation efficiency of the membrane.
Smart Images

Figure CN120603643A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite semipermeable membrane, a composite semipermeable membrane module and a fluid separation device useful for selective separation of liquid mixtures. Background Art
[0002] There are various technologies for removing substances (e.g., salts) dissolved in solvents (e.g., water), but in recent years, the use of membrane separation methods using semipermeable membranes such as reverse osmosis membranes and nanofiltration membranes has been expanding as a process for saving energy and resources.
[0003] Currently available reverse osmosis membranes and nanofiltration membranes are generally composite semipermeable membranes comprising a support membrane and a separation functional layer laminated on the support membrane. As the separation functional layer, crosslinked polyamides obtained by the polycondensation reaction of polyfunctional amines and polyfunctional acyl halides are known.
[0004] The composite semipermeable membrane of this invention is thinner because separation function layer, and therefore has the problem that separation performance reduces easily because of the friction of separation function layer.As the reason of friction, can enumerate the composite semipermeable membrane contacting each other when stacking for safekeeping after manufacturing, contact with the packaging material used for safekeeping etc.In addition, composite semipermeable membrane is mostly used with the state of the element that is assembled into the composite semipermeable membrane with more than 2 sheets and the flow path material inserted therebetween.The composite semipermeable membrane during this element assembling and the contact of the parts of assembly device or the parts of element also can be enumerated as the reason of friction.
[0005] Various methods have been disclosed for suppressing the reduction in separation performance caused by such friction. For example, Patent Document 1 discloses a method for suppressing friction of the separation functional layer by disposing a coating layer made of a polymer such as polyvinyl alcohol on the surface of the separation functional layer. Furthermore, Patent Document 2 discloses a method for suppressing the occurrence of membrane defects caused by friction of the separation functional layer by providing the separation functional layer with a sufficient amount of polyamide.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2003-200026
[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-98329 Summary of the Invention
[0010] Problems to be solved by the invention
[0011] While the method described in Patent Document 1 achieves a certain improvement in friction resistance, the presence of the coating layer reduces the water permeability of the composite semipermeable membrane. Furthermore, the method described in Patent Document 2 presents a trade-off between the amount of polyamide in the separation functional layer and the water permeability of the composite semipermeable membrane.
[0012] Therefore, an object of the present invention is to provide a composite semipermeable membrane having excellent friction resistance and good water permeability.
[0013] Means for solving problems
[0014] In order to solve the above-mentioned problems, the present invention provides the following composite semipermeable membrane, composite semipermeable membrane module, and fluid separation device.
[0015] [1] A composite semipermeable membrane comprising a supporting membrane, a separation functional layer comprising a cross-linked polyamide disposed on the supporting membrane, and a coating layer disposed on the separation functional layer.
[0016] Wherein, the developed area ratio Sdr of the coating layer side surface of the composite semipermeable membrane is 60 to 200%.
[0017] The static friction coefficient μs between the coating layer side surface of the composite semipermeable membrane and the polishing film abrasive material with a particle size of #2000 is 0.40 to 1.30.
[0018] [2] The composite semipermeable membrane according to [1] above, wherein the dynamic friction coefficient μd between the coating layer side surface of the composite semipermeable membrane and the polishing film abrasive with a particle size of #2000 is 0.25 to 0.73.
[0019] [3] The composite semipermeable membrane according to [1] or [2] above, wherein the root mean square height Sq of the surface of the composite semipermeable membrane on the coating layer side is 140 to 300 nm.
[0020] [4] The composite semipermeable membrane according to any one of [1] to [3] above, wherein the coating layer comprises at least one of a vinyl alcohol polymer and an alkylene glycol polymer.
[0021] [5] The composite semipermeable membrane according to [4] above, wherein the degree of saponification of the vinyl alcohol polymer is 96 mol% or more.
[0022] [6] The composite semipermeable membrane according to [4] or [5] above, wherein the degree of polymerization of the vinyl alcohol polymer is 100 to 1,500.
[0023] [7] The composite semipermeable membrane according to any one of [4] to [6] above, wherein the vinyl alcohol polymer is a vinyl alcohol copolymer having a structure represented by the following general formula (1).
[0024] [Chemical Formula 1]
[0025]
[0026] [In the general formula (1), X is a divalent hydrocarbon group having 2 to 6 carbon atoms, and l, m, and n are the numbers of repeating units.]
[0027] [8] The composite semipermeable membrane according to [7] above, wherein X in the general formula (1) is a divalent hydrocarbon group having 2 carbon atoms.
[0028] [9] The composite semipermeable membrane according to [8] above, wherein X in the general formula (1) is 1,2-ethylene.
[0029]
[10] The composite semipermeable membrane according to any one of [7] to [9] above, wherein the copolymerization ratio of the vinyl alcohol copolymer: n / (l+m+n) is 0.035 to 0.16.
[0030]
[11] The composite semipermeable membrane according to [4] above, wherein the molecular weight of the alkylene glycol polymer is 500 to 500,000.
[0031]
[12] A composite semipermeable membrane module comprising the composite semipermeable membrane according to any one of [1] to
[11] .
[0032]
[13] A fluid separation device comprising the composite semipermeable membrane assembly described in
[12] above.
[0033] Effects of the Invention
[0034] According to the present invention, a composite semipermeable membrane having excellent abrasion resistance and good water permeability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] [ Figure 1 ] Figure 1 Schematic diagram showing the cross-sectional structure of a composite semipermeable membrane.
[0036] [ Figure 2 ] Figure 2 Schematic diagram showing the structure of a composite semipermeable membrane having a pleated separation functional layer and a coating layer, (a) is a partial enlarged view, and (b) is an enlarged view of Y in (a).
[0037] [ Figure 3 ] Figure 3 This is a schematic diagram showing the method of the friction test of the composite semipermeable membrane.
[0038] [ Figure 4 ] Figure 4This is an example of a graph showing the static friction force Fs (N) and the dynamic friction force Fd (N) obtained by measuring the friction test of the composite semipermeable membrane. DETAILED DESCRIPTION
[0039] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments.
[0040] It should be noted that, in this specification, “mass” and “weight” have the same meaning.
[0041] 1. Composite semipermeable membrane
[0042] Figure 1 A first embodiment of the structure of the composite semipermeable membrane 1 in this embodiment is shown. The composite semipermeable membrane 1 of the present invention includes a supporting membrane 2 , a separation functional layer 3 , and a coating layer 4 .
[0043] (1-1) Support membrane
[0044] The supporting membrane included in the composite semipermeable membrane according to this embodiment includes at least a porous supporting layer. The supporting membrane is used to impart strength to the composite semipermeable membrane, and does not substantially have solute separation performance itself.
[0045] The porous supporting layer has a large number of interconnected pores. The pore diameter and pore size distribution are not particularly limited. For example, a porous supporting layer having a symmetrical structure with uniform pore diameter or an asymmetrical structure with gradually increasing pore diameter from one surface to the other surface, with the pore diameter on the surface with smaller pore diameter being 0.1 to 100 nm, is preferred.
[0046] As the raw material of the porous supporting layer, homopolymers or copolymers such as polysulfone (hereinafter also referred to as "PSf"), polyethersulfone, polyamide, polyester, cellulose-based polymer, vinyl polymer, polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfone, and polyphenylene ether can be used alone or in combination. Here, examples of the cellulose-based polymer include cellulose acetate and cellulose nitrate, and examples of the vinyl polymer include polyethylene, polypropylene, polyvinyl chloride, and polyacrylonitrile. Among them, homopolymers or copolymers such as PSf, polyamide, polyester, cellulose acetate, cellulose nitrate, polyvinyl chloride, polyacrylonitrile, polyphenylene sulfide, and polyphenylene sulfide sulfone are preferred, and cellulose acetate, PSf, polyphenylene sulfide sulfone, or polyphenylene sulfone is more preferred. PSf is particularly preferred from the perspectives of high chemical stability, mechanical stability, thermal stability, and ease of molding.
[0047] The weight-average molecular weight (hereinafter referred to as "Mw") of PSf is preferably 10,000 to 200,000, and more preferably 15,000 to 100,000. A PSf Mw of 10,000 or greater provides mechanical strength and heat resistance suitable for a porous supporting layer. On the other hand, a PSf Mw of 200,000 or less maintains an appropriate viscosity within the porous supporting layer stock solution, achieving excellent moldability.
[0048] Furthermore, the supporting membrane may have a substrate in addition to the porous supporting layer.
[0049] Examples of the base material include fabrics made from polyester polymers, polyamide polymers, polyolefin polymers, and mixtures or copolymers thereof. Among these, fabrics made from polyester polymers with high mechanical and thermal stability are preferred. The fabric may be in the form of long-fiber nonwoven fabrics or short-fiber nonwoven fabrics, with woven knitted fabrics being more preferred.
[0050] The thickness of the supporting membrane affects the strength of the composite semipermeable membrane and the packing density when it is made into an element. In order to obtain good mechanical strength and packing density, the thickness of the supporting membrane is preferably 50 to 300 μm, more preferably 100 to 250 μm. In addition, when the supporting membrane is composed of a porous supporting layer and a substrate, the thickness of the porous supporting layer is preferably 20 to 100 μm. It should be noted that the thickness of the supporting membrane can be obtained as follows: by cross-sectional observation, measurement is performed at intervals of 20 μm in a direction perpendicular to the thickness direction (the surface direction of the membrane), and the average value of the thickness at 20 locations is calculated.
[0051] (1-2) Separation functional layer
[0052] The separation functional layer disposed on the supporting membrane of the composite semipermeable membrane according to this embodiment is a layer responsible for the solute separation function and comprises a cross-linked polyamide. The proportion of the cross-linked polyamide in the separation functional layer is preferably 50% by mass or greater, more preferably 80% by mass or greater, and even more preferably 90% by mass or greater. The content of the cross-linked polyamide in the separation functional layer can generally be calculated by analysis using nuclear magnetic resonance.
[0053] The crosslinked polyamide is preferably a condensation polymer of a polyfunctional amine and a polyfunctional acid chloride. Preferably, at least one of the polyfunctional amine and the polyfunctional acid chloride comprises a trifunctional or higher compound. This provides a rigid molecular chain and a good pore structure for removing fine solutes such as hydrated ions and silica.
[0054] A polyfunctional amine is an amine having at least two primary and / or secondary amino groups in one molecule. Examples include aromatic trifunctional amines such as 1,3,5-triaminobenzene and 1,2,4-triaminobenzene; aromatic difunctional amines such as o-phenylenediamine, m-phenylenediamine (hereinafter also referred to as "m-PDA"), p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, o-diaminopyridine, m-diaminopyridine, p-diaminopyridine, 3,5-diaminobenzoic acid, 2,4-diaminobenzenesulfonic acid, 3-aminobenzylamine, and 4-aminobenzylamine; and aliphatic difunctional amines such as ethylenediamine, propylenediamine, 1,4-diaminocyclohexane, piperazine, 2,5-dimethylpiperazine, 4-aminopiperidine, and aminoethylpiperazine. These polyfunctional amines may be used alone or in combination of two or more.
[0055] From the perspectives of separation performance, water permeability, and heat resistance of the composite semipermeable membrane, the polyfunctional amine is preferably m-PDA, p-phenylenediamine, or 1,3,5-triaminobenzene. Among them, m-PDA is particularly preferred from the perspectives of ease of availability and handling.
[0056] The so-called polyfunctional acid chloride refers to an acid chloride having at least two chlorocarbonyl groups in one molecule. For example, there can be mentioned aromatic trifunctional acid chlorides such as trimesoyl chloride (hereinafter also referred to as "TMC") and trimellitic trifunctional acid chlorides, aliphatic trifunctional acid chlorides such as 1,3,5-cyclohexanetricarboxylic acid chloride, aromatic difunctional acid chlorides such as biphenyl dicarboxylic acid chloride, azophthaloyl dicarboxylic acid chloride, terephthaloyl dicarboxylic acid chloride, isophthaloyl dicarboxylic acid chloride, and 2,6-naphthalene dicarboxylic acid chloride, and aliphatic difunctional acid chlorides such as adipoyl chloride, sebacoyl chloride, and 1,4-cyclohexane dicarboxylic acid chloride. These polyfunctional acid chlorides can be used alone or in combination of two or more.
[0057] From the viewpoint of separation performance and heat resistance of the composite semipermeable membrane, the polyfunctional acid chloride is preferably a polyfunctional aromatic acid chloride having 2 to 4 chlorocarbonyl groups in one molecule. Among them, TMC is particularly preferred from the viewpoint of easy availability and handling.
[0058] (1-3) Coating layer
[0059] The covering layer included in the composite semipermeable membrane according to the present embodiment is a layer responsible for protecting the separation functional layer, and is disposed on the separation functional layer.
[0060] In the composite semipermeable membrane of the present invention, the static friction coefficient (hereinafter also referred to as "μs") between the coating layer side surface and the polishing film abrasive with a particle size of #2000 is 0.40 to 1.30.
[0061] The static friction coefficient is proportional to the static friction force, and the static friction force plays a role in preventing an object from starting to move from a stationary state. When μs is less than 1.30, the static friction force received when the composite semipermeable membrane starts to slide becomes smaller, so it is possible to reduce the damage received by the separation functional layer due to friction. On the other hand, when μs is more than 0.40, the composite semipermeable membrane becomes difficult to slide, so it is possible to be wound around the composite semipermeable membrane and processed into a spiral composite semipermeable membrane element or when the composite semipermeable membrane element is operated, the deformation (telescopic phenomenon) of the winding body caused by the composite semipermeable membrane to the axial deviation of the composite semipermeable membrane element is suppressed. μs is preferably 0.80 to 1.30, more preferably 0.95 to 1.25, and further preferably 1.08 to 1.20.
[0062] The static friction coefficient of the composite semipermeable membrane can be controlled by, for example, the heating temperature of the supporting membrane after contact with the organic solvent solution of the polyfunctional acid chloride in the polymerization step of the separation functional layer, the raw material of the coating layer, the concentration of the water-soluble polymer in the aqueous solution used to form the coating layer, etc.
[0063] The dynamic friction coefficient (hereinafter also referred to as "μd") between the coating layer side surface of the composite semipermeable membrane involved in this embodiment and the polishing film abrasive of particle size #2000 is preferably 0.25-0.73, more preferably 0.45-0.73, further preferably 0.55-0.72, and particularly preferably 0.66-0.70.
[0064] The coefficient of kinetic friction is proportional to the kinetic friction force that acts to prevent movement of a moving object. When μd is 0.73 or less, the kinetic friction force experienced by the composite semipermeable membrane during sliding is reduced, thereby reducing damage to the separation functional layer caused by friction. On the other hand, when μd is 0.25 or greater, the composite semipermeable membrane is less likely to slide, thereby suppressing expansion and contraction of the composite semipermeable membrane element.
[0065] The dynamic friction coefficient of the composite semipermeable membrane can be controlled, for example, by the heating temperature of the supporting membrane after contact with the organic solvent solution of the polyfunctional acid chloride in the polymerization step of the separation functional layer, the raw material of the coating layer, the concentration of the water-soluble polymer in the aqueous solution used to form the coating layer, etc.
[0066] The shape and thickness of the separation functional layer and the coating layer affect the separation performance and water permeability. Figure 2 A second embodiment of the structure of the composite semipermeable membrane 1 in this embodiment is shown. Figure 2As shown in (a) and (b), the separation functional layer 3 is preferably a corrugated shape having a plurality of convex portions. In addition, it is more preferred that the interior 5 of the convex portion (between the separation functional layer 3 and the supporting membrane 2) is a void. When the separation functional layer 3 has a corrugated shape, it is possible to obtain a larger surface area than when it has a flat shape, and thus it is possible to obtain high water permeability while maintaining separation performance. It should be noted that the coating layer 4 can also be formed thinly on the separation functional layer 3 to form a corrugated shape together with the separation functional layer, or have a relatively large thickness such as the corrugated shape that fills the separation functional layer 3.
[0067] As effective configurations for suppressing friction-induced degradation of the separation functional layer's performance, the shape of the composite semipermeable membrane's coating layer-side surface (developed area ratio Sdr) and the total thickness of the separation functional layer and the coating layer are described below.
[0068] The developed area ratio (hereinafter also referred to as "Sdr") of the coating layer side surface of the composite semipermeable membrane of the present invention is 60 to 200%. The developed area ratio (Sdr) is a parameter that represents the rate of increase (%) of the developed area (surface area) of the defined region relative to the area of the defined region. The smaller the value, the closer the surface shape is to being flat, and the Sdr of a completely flat surface is 0%. On the other hand, the larger the value, the more concave and convex the surface shape is. When Sdr is 60% or more, the surface area of the composite semipermeable membrane becomes larger, so that a composite semipermeable membrane with good water permeability can be obtained. However, when Sdr is 60% or more, that is, when the concave and convex of the separation functional layer surface becomes more, the convex portion of the separation functional layer is easily damaged by abrasion, and therefore the friction resistance of the composite semipermeable membrane is usually reduced. The inventors of the present application have discovered that even when Sdr is set to 60-200%, a composite semipermeable membrane exhibiting excellent friction resistance can be obtained by setting the static friction coefficient μs between the coating layer side surface of the composite semipermeable membrane and a polishing film abrasive with a particle size of #2000 to 0.40-1.30. Sdr is preferably 70-180%, and more preferably 80-150%.
[0069] The developed area ratio of the composite semipermeable membrane can be controlled, for example, by the heating temperature of the supporting membrane after contact with the organic solvent solution of the polyfunctional acid chloride in the polymerization step of the separation functional layer, the concentration of the water-soluble polymer in the aqueous solution for forming the coating layer, etc.
[0070] The root mean square height (hereinafter referred to as "Sq") of the coating layer side surface of the composite semipermeable membrane involved in this embodiment is preferably 140 to 300 nm, more preferably 145 to 270 nm, and even more preferably 150 to 240 nm. When Sq is 140 nm or greater, a composite semipermeable membrane having excellent water permeability can be obtained in proportion to the large surface area of the composite semipermeable membrane. On the other hand, when Sq is 300 nm or less, a composite semipermeable membrane exhibiting excellent friction resistance can be obtained.
[0071] The root mean square height of the coating layer side surface of the composite semipermeable membrane can be controlled, for example, by the heating temperature of the supporting membrane after contact with the organic solvent solution of the polyfunctional acid chloride in the polymerization process of the separation functional layer, the concentration of the water-soluble polymer in the aqueous solution used to form the coating layer, etc.
[0072] The total thickness T of the separation functional layer and the coating layer is preferably 10 to 100 nm, more preferably 11 to 70 nm, and further preferably 11 to 20 nm. When the total thickness T of the separation functional layer and the coating layer is 10 nm or more, a composite semipermeable membrane exhibiting good separation performance and friction resistance can be obtained. On the other hand, when the total thickness T of the separation functional layer and the coating layer is 100 nm or less, a composite semipermeable membrane having good water permeability can be obtained. Figure 2 As shown in (b), the so-called "total thickness T" refers to the thickness from the inside 5 of the convex portion to the outside when the separation functional layer 3 and the coating layer 4 overlap and become one, and the separation functional layer and the coating layer form a folded shape of multiple hollow convex portions.
[0073] In order to prevent the substance to be separated from penetrating into the composite semipermeable membrane, the separation functional layer and the coating layer are preferably disposed on the primary filtration side.
[0074] The coating layer of the composite semipermeable membrane involved in this embodiment preferably contains a water-soluble polymer. Here, the so-called "water-soluble polymer" refers to a polymer that dissolves 0.5% by mass or more in water at 25°C. The proportion of the water-soluble polymer in the coating layer is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more. By including a water-soluble polymer, it is possible to simply form a coating layer on the separation functional layer using a water-soluble polymer aqueous solution in the "(2-3) coating layer formation step" described later. In addition, generally, water-soluble polymers have excellent hydrophilicity and can suppress the reduction in water permeability caused by the coating layer, so that a composite semipermeable membrane with sufficient water permeability can be obtained.
[0075] In addition, the ratio of the water-soluble polymer in the coating layer can usually be calculated by analysis using a nuclear magnetic resonance method.
[0076] Examples of the water-soluble polymer include synthetic polymers such as polyacrylic acid, polymethacrylic acid, polyvinyl pyrrolidone, vinyl alcohol polymers, polyethyleneimine, polyallylamine, polyacrylamide, poly(N-isopropylacrylamide), polyacryloylmorpholine, poly(2-ethyl-2-oxazoline), alkylene glycol polymers, polyvinyl imidazole, and polystyrene sulfonic acid, and copolymers thereof; cellulose derivatives such as carboxymethyl cellulose, hydroxyethyl cellulose, and methyl cellulose; proteins such as gelatin and casein; dextrins; and starches such as etherified starch. These water-soluble polymers may be used alone or in combination of two or more.
[0077] From the perspective of the separation performance, water permeability and friction resistance of the composite semipermeable membrane, the water-soluble polymer is preferably at least one of a vinyl alcohol polymer and an alkylene glycol polymer, and more preferably a vinyl alcohol polymer. By utilizing a coating layer comprising at least one of a vinyl alcohol polymer and an alkylene glycol polymer to coat the composite semipermeable membrane, damage caused by friction of the separation functional layer can be suppressed. In addition, the hydroxyl groups of the vinyl alcohol polymer form hydrogen bonds with the cross-linked polyamide of the composite semipermeable membrane, so the coating layer comprising the vinyl alcohol polymer is not easy to peel off from the cross-linked polyamide, which is suitable for protecting the cross-linked polyamide from damage by friction. Thus, friction resistance can be imparted to the composite semipermeable membrane.
[0078] The degree of saponification of the vinyl alcohol polymer included in the coating layer according to this embodiment is preferably 96 mol% or greater, more preferably 98 mol% or greater. When the degree of saponification of the vinyl alcohol polymer is 96 mol% or greater, the vinyl alcohol polymer has more hydroxyl groups, forming strong hydrogen bonds with the cross-linked polyamide of the composite semipermeable membrane, thereby imparting excellent abrasion resistance to the composite semipermeable membrane.
[0079] The degree of polymerization of the vinyl alcohol polymer contained in the coating layer involved in this embodiment is preferably 100 to 1,500, and more preferably 200 to 1,200. When the degree of polymerization of the vinyl alcohol polymer is 100 or more, a coating layer having a sufficient thickness can be provided, and a composite semipermeable membrane exhibiting excellent friction resistance can be obtained. On the other hand, when the degree of polymerization of the vinyl alcohol polymer is 1,500 or less, the permeation resistance caused by the thickness of the coating layer can be suppressed, and a composite semipermeable membrane having sufficient water permeability can be obtained. In addition, by making the degree of polymerization within the above range and the vinyl alcohol polymer having sufficient water solubility, a coating layer can be simply formed on the separation functional layer using an aqueous solution of the vinyl alcohol polymer in the "(2-3) coating layer formation step" described later.
[0080] The vinyl alcohol polymer may be polyvinyl alcohol (hereinafter also referred to as "PVA") having only hydroxyl groups and acetyl groups as functional groups, or may have functional groups other than these. Examples of vinyl alcohol polymers having functional groups other than hydroxyl groups and acetyl groups include modified PVA in which hydroxyl groups are modified into carbonyl groups such as carboxyl groups and acetoacetyl groups, and vinyl alcohol copolymers copolymerized with vinylpyrrolidone or olefin units. Among these, vinyl alcohol copolymers having a structure represented by the following general formula (1) (hereinafter also referred to as "vinyl alcohol copolymers") are particularly preferred.
[0081] [Chemical Formula 2]
[0082]
[0083] In the general formula (1), X is a divalent hydrocarbon group having 2 to 6 carbon atoms, and l, m, and n are the numbers of repeating units.
[0084] The vinyl alcohol copolymer may further contain other structures other than the structure represented by the general formula (1). The proportion of the structure represented by the general formula (1) in the vinyl alcohol copolymer is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. It is particularly preferred that the copolymer be composed solely of the structure represented by the general formula (1). The proportion of the structure represented by the general formula (1) in the vinyl alcohol copolymer can generally be calculated by analysis using nuclear magnetic resonance.
[0085] For the vinyl alcohol copolymer comprising the structure represented by the general formula (1), in addition to the intermolecular hydrogen bonds between the hydroxyl groups shown by PVA, the hydrophobic interactions between hydrocarbons are also shown. Thus, compared with PVA, the intermolecular interactions are strong, so the higher-order structure is not easy to change, and it is easy to maintain hydrogen bonds with cross-linked polyamide. In addition, it is known that the vinyl alcohol copolymer represented by the general formula (1) can form a film with excellent smoothness and a small friction coefficient compared to PVA. Therefore, by using the vinyl alcohol copolymer in the coating layer, a composite semipermeable membrane with a low risk of degradation due to friction and good friction resistance can be obtained.
[0086] In the general formula (1), X is a divalent hydrocarbon group having 2 to 6 carbon atoms, for example, 1,2-ethylene (-CH2CH2-), 1,1-ethylene (-CH(CH3)-), 1,2-vinylene (-CH=CH-), trimethylene (-CH2CH2CH2-), 1,2-propylene (-CH(CH3)CH2-), tetramethylene (-CH2(CH2)2CH2-), cyclopentyl, hexamethylene (-CH2(CH2(CH2)4), etc. X in the general formula (1) is preferably a divalent hydrocarbon group having 2 carbon atoms. The general formula When X in (1) is a divalent hydrocarbon group having 2 carbon atoms, the vinyl alcohol copolymer has sufficient water solubility, and a coating layer can be easily formed on the separation functional layer using an aqueous solution of the vinyl alcohol copolymer in the "(2-3) Coating Layer Formation Step" described later. In addition, X in the general formula (1) is preferably a divalent saturated hydrocarbon group having 2 to 6 carbon atoms. When X in the general formula (1) is a divalent saturated hydrocarbon group having 2 to 6 carbon atoms, a coating layer that is not easily degraded by oxidation or the like can be formed. Among them, from the viewpoint of ease of acquisition, X in the general formula (1) is particularly preferably 1,2-ethylene.
[0087] The copolymerization ratio of the vinyl alcohol copolymer comprising the structure represented by the general formula (1): n / (l+m+n) is preferably 0.035 to 0.16, more preferably 0.040 to 0.11, and further preferably 0.042 to 0.095. When the copolymerization ratio is 0.035 or more, the vinyl alcohol copolymer exhibits strong intermolecular interactions through sufficient hydrophobic interactions, and a composite semipermeable membrane with good friction resistance can be obtained. On the other hand, when the copolymerization ratio is 0.16 or less, the vinyl alcohol copolymer has sufficient water solubility and can simply form a coating layer on the separation functional layer using an aqueous solution of the vinyl alcohol copolymer in the "(2-3) coating layer formation step" described later. It should be noted that the copolymerization ratio can usually be calculated by analysis using a nuclear magnetic resonance method.
[0088] The degree of polymerization of the vinyl alcohol copolymer: l+m+n is preferably 100 to 1,500, more preferably 200 to 1,200. When the degree of polymerization of the vinyl alcohol copolymer is 100 or more, a coating layer having a sufficient thickness can be provided, and a composite semipermeable membrane exhibiting excellent friction resistance can be obtained. On the other hand, when the degree of polymerization of the vinyl alcohol copolymer is 1,500 or less, the permeation resistance caused by the thickness of the coating layer can be suppressed, and a composite semipermeable membrane having sufficient water permeability can be obtained. In addition, when the degree of polymerization is within the above range, the vinyl alcohol copolymer has sufficient water solubility, and a coating layer can be simply formed on the separation functional layer using an aqueous solution of the vinyl alcohol copolymer in the "(2-3) Coating Layer Formation Step" described later.
[0089] The molecular weight of the alkylene glycol polymer included in the coating layer according to this embodiment is preferably 500 to 500,000, more preferably 700 to 100,000, and even more preferably 800 to 10,000. When the degree of polymerization of the alkylene glycol polymer is 500 or greater, a coating layer having a sufficient thickness can be provided, resulting in a composite semipermeable membrane exhibiting excellent abrasion resistance. On the other hand, when the degree of polymerization of the alkylene glycol polymer is 500,000 or less, the reduction in water permeability due to the thickness of the coating layer can be suppressed, resulting in a composite semipermeable membrane having sufficient water permeability.
[0090] The alkylene glycol polymer preferably has a terminal functional group such as a carboxyl group, an amino group, an acetoacetyl group, or a glycidyl group that is reactive with the functional group of the cross-linked polyamide. By having these terminal functional groups in the alkylene glycol polymer, a coating layer can be easily formed on the separation functional layer using an aqueous solution of the alkylene glycol polymer.
[0091] The water-soluble polymer contained in the coating layer is preferably insolubilized so as not to dissolve when the composite semipermeable membrane is used. Examples of methods for insolubilizing the water-soluble polymer in the coating layer include methods in which the water-soluble polymer forms a non-covalent bond such as a hydrogen bond or an ionic bond with a cross-linked polyamide and is fixed to the separation functional layer; methods in which the water-soluble polymer forms a covalent bond with the cross-linked polyamide by a reaction between functional groups or cross-linking with a cross-linking agent and is fixed to the separation functional layer; methods in which the water-soluble polymer forms a covalent bond with each other by cross-linking with a cross-linking agent and forms a three-dimensional structure and is insolubilized; and so on. Among these, methods in which the water-soluble polymer forms a covalent bond with the cross-linked polyamide by a reaction between functional groups or cross-linking with a cross-linking agent and is fixed to the separation functional layer are more preferred from the perspective of enabling long-term, continuous, and stable operation.
[0092] (1-4) NaCl removal rate and membrane permeation flux
[0093] The NaCl removal rate of the composite semipermeable membrane of this embodiment is preferably 99.55% or higher, more preferably 99.65% or higher, and even more preferably 99.75% or higher. Furthermore, the membrane permeation flux during manufacture of the composite semipermeable membrane is preferably 1.00 m / d or higher, more preferably 1.15 m / d or higher, and even more preferably 1.30 m / d or higher. By ensuring that the membrane performance of the composite semipermeable membrane is within the above range, it can be preferably used as a separation membrane for separation purposes such as salts.
[0094] Furthermore, the NaCl removal rate of the composite semipermeable membrane after the friction test is preferably 99.25% or greater, more preferably 99.35% or greater, and even more preferably 99.40% or greater. By ensuring that the membrane performance after the friction test of the composite semipermeable membrane is within the above range, it can be preferably used as a composite semipermeable membrane having excellent friction resistance. The friction test method is described in "(3) Friction Test and Friction Coefficient" below.
[0095] 2. Method for manufacturing composite semipermeable membrane
[0096] The method for producing the composite semipermeable membrane according to the present embodiment is not particularly limited as long as a composite semipermeable membrane satisfying the above-mentioned desired characteristics can be obtained. For example, the composite semipermeable membrane can be produced by the following method.
[0097] (2-1) Formation of Supporting Film
[0098] As a method for forming the supporting membrane, a known method can be appropriately used. Hereinafter, a case where PSf is used as a raw material for the porous supporting layer will be described as an example.
[0099] First, PSf is dissolved in a good solvent for PSf to prepare a porous supporting layer stock solution. As a good solvent for PSf, N,N-dimethylformamide (hereinafter also referred to as "DMF") is preferred.
[0100] The PSf concentration in the porous supporting layer stock solution is preferably 10-25% by mass, more preferably 12-20% by mass. By adjusting the PSf concentration in the porous supporting layer stock solution within this range, both the strength and water permeability of the resulting porous supporting layer can be achieved. It should be noted that the preferred range of the raw material concentration in the porous supporting layer stock solution can be appropriately adjusted depending on the raw materials, good solvent, etc. used.
[0101] Next, the obtained porous supporting layer stock solution was applied to the surface of the substrate, and the substrate was immersed in a coagulation bath containing a PSf non-solvent.
[0102] The non-solvent for PSf contained in the coagulation bath is preferably water, for example. By contacting the porous supporting layer stock solution coated on the substrate surface with the coagulation bath containing the non-solvent for PSf, the porous supporting layer stock solution is coagulated due to non-solvent-induced phase separation, thereby obtaining a supporting membrane having a porous supporting layer formed on the substrate surface.
[0103] The coagulation bath may consist solely of a non-solvent for PSf, or may contain a good solvent for PSf within a range capable of coagulating the porous supporting layer stock solution.
[0104] The solvent remaining in the supporting membrane can be removed by washing the obtained supporting membrane before forming the separation functional layer.
[0105] (2-2) Separation Functional Layer Polymerization Step
[0106] Next, a separation functional layer comprising cross-linked polyamide is formed on the supporting membrane.
[0107] The method for forming a separation functional layer comprising a cross-linked polyamide is described below, using as an example a method for polymerizing and curing a polyfunctional amine and a polyfunctional acid chloride on the supporting membrane obtained in "(2-1) Formation of Support Membrane." Interfacial polymerization is the most preferred polymerization method from the perspectives of productivity and performance. The interfacial polymerization process is described below.
[0108] The interfacial polymerization process comprises: (a) a process of bringing an aqueous solution containing a polyfunctional amine into contact with a supporting membrane; (b) a process of bringing an organic solvent solution containing a polyfunctional acid chloride into contact with the supporting membrane after contact with the aqueous solution containing the polyfunctional amine; (c) a process of dehydrating the organic solvent solution after contact; and (d) a process of washing the composite semipermeable membrane from which the organic solvent solution has been dehydrated with hot water.
[0109] In step (a), the aqueous solution contains at least a polyfunctional amine. Examples of the polyfunctional amine include the polyfunctional amines exemplified in "(1-2) Separation functional layer".
[0110] The concentration of the polyfunctional amine in the aqueous solution is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, and even more preferably 1.0 to 10% by mass. A polyfunctional amine concentration of 0.1% by mass or greater can form a separation functional layer with solute separation performance. On the other hand, a polyfunctional amine concentration of 20% by mass or less can form a separation functional layer with excellent water permeability.
[0111] Furthermore, the aqueous solution may contain compounds such as a surfactant and an antioxidant as needed, as long as they do not inhibit polymerization.
[0112] The aqueous solution is preferably brought into uniform and continuous contact with the supporting membrane. Specifically, examples include coating the supporting membrane with the aqueous solution of a polyfunctional amine or immersing the supporting membrane in the aqueous solution. The contact time between the supporting membrane and the aqueous solution is preferably 1 second to 10 minutes, more preferably 3 seconds to 3 minutes.
[0113] After the aqueous solution is brought into contact with the supporting membrane, it is preferably thoroughly dehydrated to prevent any droplets from remaining on the supporting membrane. This thorough dehydration prevents residual droplets from forming membrane defects after the separation functional layer is formed, potentially reducing separation performance. Examples of dehydration methods include holding the supporting membrane vertically after contact with the aqueous solution to allow excess solution to flow naturally downward, and forcibly dehydrating the membrane by blowing a stream of nitrogen or other substances through an air nozzle. Alternatively, the membrane surface can be dried after dehydration to remove some of the water from the aqueous solution.
[0114] In step (b), examples of the polyfunctional acid chloride include the polyfunctional acid chlorides exemplified in "(1-2) Separation functional layer".
[0115] The organic solvent is preferably immiscible with water, capable of dissolving the polyfunctional acid chloride, non-corrosive to the supporting membrane, and inactive toward polyfunctional amines and polyfunctional acid chlorides. Examples of the organic solvent include hydrocarbon compounds such as n-nonane, n-decane, n-undecane, n-dodecane, isooctane, isodecane, and isododecane, and mixed solvents thereof.
[0116] The concentration of the polyfunctional acyl chloride in the organic solvent solution is preferably 0.01 to 10 mass %, more preferably 0.02 to 4 mass %, further preferably 0.03 to 2 mass %. When the concentration of the polyfunctional acyl chloride is 0.01 mass % or more, polymerization can be carried out with sufficient reaction speed. On the other hand, when the concentration of the polyfunctional acyl chloride is 10 mass % or less, the generation of the side reaction in the polymerization can be suppressed. In addition, in the organic solvent solution, as long as it does not hinder polymerization, compounds such as surfactants can be included as needed.
[0117] The organic solvent solution of the polyfunctional acid chloride is preferably brought into uniform and continuous contact with the supporting membrane after contact with the aqueous polyfunctional amine solution. Specifically, for example, a method can be employed in which the organic solvent solution of the polyfunctional acid chloride is coated onto the supporting membrane after contact with the aqueous polyfunctional amine solution. The contact time between the supporting membrane after contact with the aqueous polyfunctional amine solution and the organic solvent solution of the polyfunctional acid chloride is preferably 3 seconds to 10 minutes, more preferably 5 seconds to 3 minutes.
[0118] If necessary, the supporting membrane may be heat-treated after contact with the organic solvent solution of the polyfunctional acid chloride. When heat-treated, the heating temperature is preferably 35-180°C, more preferably 50-160°C, and even more preferably 60-150°C. The optimal heating time varies depending on the temperature of the membrane surface, which serves as the reaction site, but is preferably 5 seconds or longer, and more preferably 10 seconds or longer.
[0119] In step (c), the organic solvent solution on the composite semipermeable membrane after the polymerization reaction is removed by degassing. Examples of degassing methods include a method in which the membrane is held vertically and excess organic solvent solution is allowed to flow down and be removed naturally; a method in which the organic solvent is dried and removed by blowing air with a blower; and a method in which excess organic solvent solution is removed using a mixed fluid of water and air.
[0120] In step (d), the composite semipermeable membrane from which the organic solvent has been removed is cleaned with hot water. The temperature of the hot water is preferably 40 to 95°C, more preferably 60 to 95°C. When the temperature of the hot water is 40°C or above, the unreacted products and oligomers remaining in the membrane can be fully removed. On the other hand, when the temperature of the hot water is 95°C or below, the shrinkage of the composite semipermeable membrane does not increase, and good water permeability can be maintained. It should be noted that the preferred range of the temperature of the hot water can be appropriately adjusted according to the polyfunctional amine or polyfunctional acid chloride used.
[0121] (2-3) Coating Layer Formation Step
[0122] Next, a coating layer is formed on the separation functional layer.
[0123] The method of forming a coating layer on the separation functional layer will be described as an example of a method of insolubilizing a water-soluble polymer by cross-linking the cross-linked polyamide contained in the separation functional layer obtained in the "(2-2) Separation functional layer polymerization step".
[0124] The steps of forming the coating layer include: (e) a step of bringing an aqueous solution containing a water-soluble polymer and a cross-linking agent into contact with the separation functional layer; (f) a step of cross-linking the water-soluble polymer with the cross-linked polyamide and fixing them on the separation functional layer; (g) a step of removing excess aqueous solution; and (h) a step of cleaning the composite semipermeable membrane.
[0125] In step (e), the aqueous solution contains a water-soluble polymer and a cross-linking agent. Examples of the water-soluble polymer include the water-soluble polymers exemplified in "(1-3) Coating Layer".
[0126] The concentration of the water-soluble polymer in the aqueous solution is preferably 0.3 to 10% by mass, more preferably 0.35 to 8% by mass, and even more preferably 0.4 to 5% by mass. When the concentration of the water-soluble polymer is 0.3% by mass or greater, a coating layer having a sufficient thickness can be provided, and a composite semipermeable membrane exhibiting excellent abrasion resistance can be obtained. On the other hand, when the concentration of the water-soluble polymer is 10% by mass or less, the coating layer is not excessively thick, and a composite semipermeable membrane having sufficient water permeability can be obtained.
[0127] A "crosslinking agent" is a compound that reacts with the functional groups of the water-soluble polymer and the functional groups of the crosslinked polyamide to form covalent bonds. When a vinyl alcohol polymer is used as the water-soluble polymer, examples of the crosslinking agent include polyaldehydes such as succinaldehyde, glutaraldehyde, and terephthalaldehyde.
[0128] The concentration of the crosslinking agent in the aqueous solution is preferably 0.01 to 5% by mass, more preferably 0.02 to 1% by mass, and even more preferably 0.05 to 0.5% by mass. When the concentration of the crosslinking agent is 0.01% by mass or greater, the water-soluble polymer and the crosslinked polyamide form covalent bonds, thereby insolubilizing the water-soluble polymer. On the other hand, when the concentration of the crosslinking agent is 5% by mass or less, the rapid crosslinking reaction is suppressed, allowing for the formation of a uniform coating layer.
[0129] The aqueous solution may contain compounds such as catalysts as needed. When a vinyl alcohol polymer is used as the water-soluble polymer and a polyaldehyde is used as the crosslinking agent, examples of the catalyst include inorganic acids such as hydrochloric acid and sulfuric acid.
[0130] The aqueous solution is preferably brought into uniform and continuous contact with the separation functional layer. Specifically, for example, the aqueous solution can be applied to the separation functional layer. The contact time between the separation functional layer and the aqueous solution is preferably 5 seconds to 10 hours, more preferably 10 seconds to 1 hour.
[0131] In step (f), the water-soluble polymer is cross-linked with the cross-linked polyamide of the separation functional layer to be insolubilized. The cross-linking method can be appropriately selected according to the water-soluble polymer and cross-linking agent used. When a vinyl alcohol polymer is used as the water-soluble polymer and a polyaldehyde is used as the cross-linking agent, thermal cross-linking is preferably used as the cross-linking method. As a method of thermal cross-linking, for example, a method of heating the aqueous solution and the composite semipermeable membrane by blowing hot air with a blower can be cited. The temperature of the hot air is preferably 30 to 120°C, more preferably 40 to 80°C. When the temperature of the hot air is above 30°C, the water-soluble polymer forms a covalent bond with the cross-linked polyamide and the water-soluble polymer can be insolubilized. On the other hand, when the temperature of the hot air is below 120°C, the rapid cross-linking reaction can be suppressed to form a uniform coating layer, and the shrinkage of the composite semipermeable membrane will not increase, so that good water permeability can be maintained.
[0132] In step (g), the aqueous solution on the composite semipermeable membrane after the cross-linking reaction is removed by dehydration. Examples of dehydration methods include a method in which the membrane is held vertically to allow the excess aqueous solution to flow down and be removed naturally; a method in which the aqueous solvent is dried and removed by blowing air with a blower; and the like.
[0133] In step (h), the composite semipermeable membrane from which the aqueous solution has been removed is washed with water. The temperature of the water used for washing is preferably 15 to 70°C, more preferably 20 to 50°C. When the temperature of the water is above 15°C, the unreacted substances, catalysts, etc. remaining in the composite semipermeable membrane can be fully removed. On the other hand, when the temperature of the water is below 70°C, the shrinkage of the composite semipermeable membrane will not increase, and good water permeability can be maintained. It should be noted that the preferred range of the water temperature can be appropriately adjusted according to the type of water-soluble polymer and cross-linking agent used.
[0134] In addition, the composite semipermeable membrane may be subjected to a hydrophilization treatment as required. Examples of the hydrophilization treatment method include contacting the composite semipermeable membrane with an aqueous surfactant solution such as polyoxyethylene octylphenyl ether or sodium n-dodecylbenzenesulfonate, or an aqueous alcohol solution such as methanol, ethanol, or isopropyl alcohol.
[0135] 3. Application of composite semipermeable membrane
[0136] The composite semipermeable membrane of this embodiment is suitable for use as a spiral composite semipermeable membrane element, wound around a cylindrical water collection pipe having multiple holes therethrough, along with a feed water flow path material such as a plastic mesh, a permeate water flow path material such as a tricot fabric, and, if necessary, a membrane for improving pressure resistance. Furthermore, a composite semipermeable membrane module can be constructed by connecting these elements in series or in parallel and housing them in a pressure vessel.
[0137] Furthermore, the composite semipermeable membrane, its elements, and modules can be combined with a pump to supply feed water, a device to pre-treat the feed water, and the like to form a fluid separation device. This fluid separation device can separate the feed water into permeate water, such as drinking water, and concentrated water that has not permeated the membrane, thereby obtaining target water.
[0138] Examples of the supply water to be treated using the composite semipermeable membrane involved in this embodiment include liquid mixtures containing 500 mg / L to 100 g / L of total dissolved solids (Total Dissolved Solids: hereinafter also referred to as "TDS"), such as seawater, brackish water, and wastewater. Generally, TDS refers to the total dissolved solids content and is expressed as "mass / volume" or "mass ratio." By definition, it is calculated based on the weight of the residue after evaporating a solution filtered through a 0.45 micron filter at a temperature of 39.5 to 40.5°C, but it is more convenient to convert it based on the practical salinity (S).
[0139] When the operating pressure of the fluid separation device is high, the solute removal rate is improved, but the energy required for operation is also increased. In addition, if the durability of the composite semipermeable membrane is taken into consideration, the operating pressure when the treated water passes through the composite semipermeable membrane is preferably 0.5 to 10 MPa. When the supply water temperature becomes higher, the solute removal rate decreases, but as the supply water temperature decreases, the water permeability also decreases. Therefore, the supply water temperature is preferably 5 to 45°C. In addition, in the case of supply water with a high solute concentration such as seawater, when the pH of the supply water becomes high, scale such as magnesium may be generated. In addition, since operation under high pH conditions may cause degradation of the composite semipermeable membrane, it is preferably operated in the neutral region.
[0140] Example
[0141] The present invention will be described below with reference to specific examples, but the present invention is not limited to these examples.
[0142] The physical properties of the composite semipermeable membrane of the present invention were measured by the following methods.
[0143] (1) Membrane permeation flux
[0144] Evaluation water (hereinafter referred to as "evaluation water") prepared at a NaCl concentration of 2,000 mg / L, 25°C, and pH 7 was supplied to a composite semipermeable membrane with a diameter of 75 mm at an operating pressure of 1.55 MPa. After 2 hours of operation, permeate water was collected for 15 minutes. The permeate water volume (m 3 ) and converted into per unit membrane area (m 2 ) and unit time (d), and calculate the membrane permeation flux (m / d).
[0145] (2) NaCl removal rate
[0146] In the membrane filtration test of "(1) Membrane permeation flux," the conductivity of the evaluation water and the permeate was measured using a multifunctional water quality meter (MM-60R, manufactured by DKK Toa Co., Ltd.), and the NaCl concentration (practical salinity) of each was measured. The NaCl removal rate (%) was calculated based on the obtained NaCl concentration using the following formula (1). Note that the value rounded off to the third decimal place was used.
[0147] NaCl removal rate (%) = 100 × {1-(NaCl concentration in permeate water / NaCl concentration in evaluation water)} ···Formula (1)
[0148] (3) Friction test and friction coefficient
[0149] The friction test was performed as follows.
[0150] Cut the composite semipermeable membrane into 10cm×10cm squares and wash it with 70°C distilled water for 5 minutes. Attach the washed composite semipermeable membrane to a 2.09kg (20.5N) rectangular parallelepiped (bottom 12cm×13cm square) weight in a manner that the coating layer or separation functional layer becomes the front side, and deliquify the membrane surface by blowing nitrogen from an air nozzle. In addition, a polishing film grinding material (manufactured by TRUSCO Nakayama Co., Ltd.; TLF-2000, particle size #2000) is attached to a flat metal plate in a manner that the grinding surface becomes the front side. As Figure 3 As shown, a weight 8 is placed on the polished surface of a polishing film abrasive 10 attached to a metal plate 11 so as to contact the entire coating layer or separation functional layer of the composite semipermeable membrane 9. A rope is attached to one side of the axial direction (horizontal direction) of the weight 8, and the other side of the rope is connected to a tensile testing machine 6 (manufactured by A&D Co., Ltd.; RTG-1210). A pulley 7 is interposed between the weight 8 and the tensile testing machine 6 in such a way that the rope is vertically bent. The weight 8 is stretched together with the composite semipermeable membrane 9 by the tensile testing machine 6 under the following conditions.
[0151] Tensile speed: 100mm / min
[0152] Stretching distance: 120mm
[0153] Measurement room temperature: 25℃
[0154] like Figure 4 As shown, the maximum load in the friction test is defined as the static friction force Fs (N), and the average load from the start of the relative deflection motion between the contact surfaces to the initial 60 mm is defined as the dynamic friction force Fd (N).
[0155] The composite semipermeable membrane was replaced and the same measurement was repeated 5 times. Based on the average values of the static friction force Fs (N) and the dynamic friction force Fd (N) and the load Fp (N) of the weight, the static friction coefficient μs and the dynamic friction coefficient μd were calculated based on the following formulas (2) and (3).
[0156] μs=Fs / Fp···Formula (2)
[0157] μd=Fd / Fp ···Formula (3)
[0158] Furthermore, using the composite semipermeable membranes subjected to the friction test, the NaCl removal rate (%) after the friction test was calculated by the method described in "(2) NaCl removal rate". All five composite semipermeable membranes subjected to the friction test were measured, and the average value was used as the NaCl removal rate after the friction test.
[0159] (4) Total thickness of the separation functional layer and the coating layer T
[0160] The composite semipermeable membrane was cut into 3 cm × 3 cm squares and immersed in distilled water at 25°C for 24 hours. After the impregnation, the composite semipermeable membrane was embedded in epoxy resin, stained with osmium tetroxide, and extremely thin slices were cut out using a microtome as measurement samples. For the obtained sample, the cross section of the composite semipermeable membrane was used as the observation surface and observed using a scanning transmission electron microscope (made by Hitachi, Ltd.; HD2700). Using an image acquired at a magnification of 1 million times, the shortest distance from a certain point on the external surface of the separation functional layer or the coating layer to the internal surface was measured. For 10 randomly selected protrusions, 5 points were measured on one protrusion, and the average value was taken as the total thickness T (nm) of the separation functional layer and the coating layer.
[0161] (5) Development area ratio Sdr, root mean square height Sq
[0162] The composite semipermeable membrane was cut into 3 cm × 3 cm squares and immersed in distilled water at 25°C for 24 hours. The immersed composite semipermeable membrane was observed under the following conditions using an atomic force microscope (Bruker; Dimension FastScan) with the coating layer or separation functional layer disposed on the surface as the measurement surface, while wet with distilled water. For 10 randomly selected locations, the developed area ratio and root mean square height were calculated according to ISO 25178:2014 Surface Properties (Surface Roughness Determination), and the average values were used as the developed area ratio Sdr (%) and root mean square height Sq (nm).
[0163] Scanning Mode: Nanomechanical Mapping in Water
[0164] Probe: Silicon cantilever (Bruker; Scan Asyst-Fluid)
[0165] Maximum load: 5nN
[0166] Scanning range: 10μm×10μm
[0167] Scan speed: 1Hz
[0168] Number of pixels: 512×512
[0169] Measurement environment: distilled water
[0170] Measurement temperature: 25°C
[0171] (6) Weight average molecular weight
[0172] The weight average molecular weight (in terms of polystyrene) of PSf was measured using gel permeation chromatography (manufactured by Tosoh Corporation; HLC-8022). Specific measurement conditions are as follows.
[0173] Chromatographic columns: 2 TSK gel SuperHM-H (manufactured by Tosoh Corporation; inner diameter 6.0 mm, length 15 cm)
[0174] Eluent: LiBr / N-methylpyrrolidone solution (10 mM)
[0175] Sample concentration: 0.1 mass%
[0176] Flow rate: 0.5mL / min
[0177] Temperature: 40℃
[0178] The raw materials of the composite semipermeable membranes used in Examples and Comparative Examples are summarized below.
[0179] PSf (manufactured by Solvay Specialty Polymers Japan Co., Ltd.; UdelP-3500, Mw80,000)
[0180] DMF (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0181] Polyester long fiber nonwoven fabric (thickness 90 μm; density 0.42 g / cm 3 )
[0182] m-PDA (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0183] TMC (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0184] n-Decane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0185] Sodium nitrite (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0186] Sodium sulfite (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0187] Sulfuric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0188] Polyacrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; Mw 25,000)
[0189] 4-(4,6-Dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholine chloride (hereinafter also referred to as "DMT-MM") (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0190] PVA1 (manufactured by Sigma-Aldrich; saponification degree 99.5 mol%, polymerization degree 2,600)
[0191] PVA2 (manufactured by Sigma-Aldrich; saponification degree 98.0-99.0 mol%, polymerization degree 900)
[0192] Vinyl alcohol copolymer 1 (manufactured by Kuraray Co., Ltd.; EXCEVAL RS-2117, saponification degree 97.5-99.0 mol%, polymerization degree 1,700, ethylene copolymerization ratio 0.030)
[0193] Vinyl alcohol copolymer 2 (manufactured by Kuraray Co., Ltd.; EXCEVAL AQ-4104, saponification degree 98.0-99.0 mol%, polymerization degree 400, ethylene copolymerization ratio 0.059)
[0194] Vinyl alcohol copolymer 3 (manufactured by Kuraray Co., Ltd.; EXCEVAL HR-3010, saponification degree 99.0-99.4 mol%, polymerization degree 1,000, ethylene copolymerization ratio 0.045)
[0195] Vinyl alcohol copolymer 4 (manufactured by Kuraray Co., Ltd.; EXCEVAL RS-1717, saponification degree 92.0-94.0 mol%, polymerization degree 1,700, ethylene copolymerization ratio 0.028)
[0196] Glutaraldehyde (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0197] Isopropyl alcohol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0198] Alkylene glycol polymer 1 (manufactured by Nagase Chemtex Co., Ltd.; DENACOL EX-171, molecular weight 900)
[0199] Alkylene glycol polymer 2 (manufactured by Nagase Chemtex Co., Ltd.; DENACOL EX-861, molecular weight 1100)
[0200] [Comparative Example 1]
[0201] A porous supporting layer stock solution was prepared by dissolving 15% by mass of PSf and 85% by mass of DMF at 100°C. This porous supporting layer stock solution was applied to the surface of a polyester long-fiber nonwoven fabric at 25°C. After 3 seconds, the fabric was coagulated by immersion in a coagulation bath of 25°C distilled water for 30 seconds. The fabric was then rinsed with 80°C hot water for 2 minutes. This produced a supporting membrane in which a porous supporting layer made of PSf was formed on the surface of the polyester long-fiber nonwoven fabric serving as a substrate. The thickness of the porous supporting layer in the resulting supporting membrane was 30 μm.
[0202] Next, the obtained supporting membrane was immersed in a 3% by mass aqueous solution of m-PDA for 2 minutes, the supporting membrane was slowly pulled up in the vertical direction, and nitrogen was blown from the air nozzle to remove excess aqueous solution from the surface of the supporting membrane. Under an environment controlled at 25°C, 20 ml of a 25°C n-decane solution containing 0.12% by mass of TMC was applied so as to completely wet the surface of the supporting membrane and allowed to stand for 1 minute to form a separation functional layer by interfacial polymerization. Then, the obtained membrane was kept vertically for 30 seconds, the excess solution was dehydrated and removed, and then washed with hot water at 80°C for 2 minutes. Furthermore, the washed membrane was immersed in a 0.3% by mass aqueous solution of sodium nitrite at 35°C and pH 3 for 1 minute, and then immersed in a 0.1% by mass aqueous solution of sodium sulfite for 2 minutes to obtain a composite semipermeable membrane.
[0203] [Comparative Example 2]
[0204] The composite semipermeable membrane obtained in Comparative Example 1 was immersed in an aqueous solution containing 0.01% by mass of polyacrylic acid and 0.1% by mass of DMT-MM for 6 hours at a controlled temperature of 20°C to form a coating layer on the separation functional layer. The composite semipermeable membrane was then held vertically, and the excess aqueous solution was drained and removed. The membrane was then rinsed with 40°C water for 2 minutes.
[0205] [Comparative Example 3]
[0206] The surface of the separation functional layer of the composite semipermeable membrane obtained in Comparative Example 1 was brought into contact with the entire surface under an environment controlled at 20°C, containing a solution (isopropyl alcohol / water = 3 / 7) of 0.25% by mass of PVA1 (99.5% by mole of saponification degree, 2,600 degree of polymerization). In a state where the aqueous solution remained on the surface of the separation functional layer, it was kept at 100°C for 5 minutes, and the solution was brought into contact again and kept at 130°C for 5 minutes to form a coating layer on the separation functional layer. Then, it was washed with water at 20°C for 2 minutes. Finally, the composite semipermeable membrane was immersed in a 14% by mass aqueous solution of isopropyl alcohol at 20°C for 5 minutes to perform a hydrophilic treatment.
[0207] [Comparative Example 4]
[0208] The surface of the separation functional layer of the composite semipermeable membrane obtained in Comparative Example 1 was brought into contact with the entire surface of an aqueous solution containing 0.15% by mass of vinyl alcohol copolymer 1 (EXCEVAL RS-2117), 0.1% by mass of glutaraldehyde, and 0.1% by mass of sulfuric acid under an environment controlled at 20°C. While the aqueous solution remained on the surface of the separation functional layer, hot air at 70°C was blown onto the composite semipermeable membrane for 1 minute, thereby forming a coating layer on the separation functional layer. Then, the composite semipermeable membrane was held vertically, and the excess aqueous solution was dehydrated and removed, and then washed with water at 20°C for 2 minutes. Finally, the composite semipermeable membrane was immersed in a 14% by mass aqueous solution of isopropyl alcohol at 20°C for 5 minutes to perform a hydrophilic treatment.
[0209] [Example 1]
[0210] The surface of the separation functional layer of the composite semipermeable membrane obtained in Comparative Example 1 was brought into contact with the entire surface of an aqueous solution containing 2.0% by mass of PVA2 (98.0-99.0% by mole of saponification, 900% by degree of polymerization), 0.5% by mass of glutaraldehyde, and 0.1% by mass of sulfuric acid under an environment controlled at 20°C. In a state where an aqueous solution remained on the surface of the separation functional layer, hot air at 70°C was blown toward the composite semipermeable membrane for 3 minutes, thereby forming a coating layer on the separation functional layer. Then, the composite semipermeable membrane was made vertical, and the excess aqueous solution was deliquated and removed, and washed with water at 20°C for 2 minutes. Finally, the composite semipermeable membrane was immersed in a 14% by mass aqueous solution of isopropyl alcohol at 20°C for 5 minutes for hydrophilization.
[0211] [Example 2]
[0212] A coating layer was formed on the separation functional layer to perform a hydrophilic treatment in the same manner as in Example 1, except that an aqueous solution containing 0.5% by mass of vinyl alcohol copolymer 2 (EXCEVAL AQ-4104), 0.3% by mass of glutaraldehyde, and 0.1% by mass of sulfuric acid was used and the blowing time of hot air at 70°C was set to 1 minute.
[0213] [Example 3]
[0214] A coating layer was formed on the separation functional layer and hydrophilic treatment was performed in the same manner as in Example 2 except that an aqueous solution containing 0.8 mass % of vinyl alcohol copolymer 3 (EXCEVAL HR-3010), 0.4 mass % of glutaraldehyde, and 0.1 mass % of sulfuric acid was used.
[0215] [Example 4]
[0216] A coating layer was formed on the separation functional layer and hydrophilic treatment was performed in the same manner as in Example 2 except that an aqueous solution containing 1.1 mass % of vinyl alcohol copolymer 1 (EXCEVAL RS-2117), 0.4 mass % of glutaraldehyde, and 0.1 mass % of sulfuric acid was used.
[0217] [Example 5]
[0218] A coating layer was formed on the separation functional layer and hydrophilic treatment was performed in the same manner as in Example 2 except that an aqueous solution containing 0.4 mass % of vinyl alcohol copolymer 4 (EXCEVAL RS-1717), 0.2 mass % of glutaraldehyde, and 0.1 mass % of sulfuric acid was used.
[0219] [Example 6]
[0220] A coating layer was formed on the separation functional layer and hydrophilic treatment was performed in the same manner as in Example 2, except that an aqueous solution containing 0.7 mass% of PVA2 (saponification degree 98.0-99.0 mol%, polymerization degree 900), 0.3 mass% of vinyl alcohol copolymer 3 (EXCEVAL HR-3010), 0.4 mass% of glutaraldehyde, and 0.1 mass% of sulfuric acid was used.
[0221] [Example 7]
[0222] A coating layer was formed on the separation functional layer and hydrophilic treatment was performed in the same manner as in Example 1, except that the composite semipermeable membrane obtained in Comparative Example 2 and an aqueous solution containing 0.3% by mass of vinyl alcohol copolymer 3 (EXCEVAL HR-3010), 0.2% by mass of glutaraldehyde, and 0.1% by mass of sulfuric acid were used.
[0223] [Example 8]
[0224] The surface of the separation functional layer of the composite semipermeable membrane obtained in Comparative Example 1 was contacted with an aqueous solution containing 1.2 weight percent of alkylene glycol polymer 1 (DENACOL EX-171) for 15 minutes under a controlled temperature of 20°C, thereby forming a coating layer on the separation functional layer. The composite semipermeable membrane was then held vertically, and the excess aqueous solution was removed by draining, followed by rinsing with 20°C water for 2 minutes.
[0225] [Example 9]
[0226] A coating layer was formed on the separation functional layer by the same method as in Example 6 except that an aqueous solution containing 0.8 mass % of an alkylene glycol polymer 2 (DENACOL EX-861) was used, and the coating layer was deliquescence and washing were performed.
[0227] The structures of the composite semipermeable membranes obtained in Comparative Examples 1 to 4 and Examples 1 to 9 are shown in Table 1, and their properties are shown in Table 2.
[0228] [Table 1]
[0229] Table 1
[0230] [Table 2]
[0231] Table 2
[0232]
[0233] As shown in Table 2, the composite semipermeable membranes of Examples 1 to 9 exhibited superior abrasion resistance and water permeability compared to the composite semipermeable membranes of Comparative Examples 1 to 4.
[0234] Furthermore, a comparison between Examples 2 to 3, 6, and 9 and Example 8 reveals that more excellent friction resistance is exhibited by setting μs to 1.08 to 1.20.
[0235] The present invention is described in detail using specific embodiments, but it is obvious to those skilled in the art that various changes and modifications can be made without departing from the intention and scope of the present invention. It should be noted that this application is based on Japanese patent application (Special Application No. 2023-015305) filed on February 3, 2023, and its entirety is incorporated herein by reference.
[0236] Description of Reference Numerals
[0237] 1 Composite semipermeable membrane
[0238] 2 Support membrane
[0239] 3 Separation functional layer
[0240] 4 Coating layer
[0241] 5 Inside the convex part
[0242] 6 Tensile testing machine
[0243] 7 Pulley
[0244] 8 weights
[0245] 9 Composite semipermeable membrane
[0246] 10 polishing film abrasive material (grit size #2000)
[0247] 11 Metal Plate
Claims
1. A composite semipermeable membrane comprising a supporting membrane, a separation functional layer comprising a cross-linked polyamide disposed on the supporting membrane, and a coating layer disposed on the separation functional layer. in, The developed area ratio Sdr of the coating layer side surface of the composite semipermeable membrane is 60 to 200%, The static friction coefficient μs between the coating layer side surface of the composite semipermeable membrane and the polishing film abrasive material with a particle size of #2000 is 0.40 to 1.
30.
2. The composite semipermeable membrane according to claim 1, wherein The dynamic friction coefficient μd between the coating layer side surface of the composite semipermeable membrane and the polishing film abrasive material with a particle size of #2000 is 0.25 to 0.
73.
3. The composite semipermeable membrane according to claim 1 or 2, wherein The root mean square height Sq of the coating layer side surface of the composite semipermeable membrane is 140 to 300 nm.
4. The composite semipermeable membrane according to claim 1 or 2, wherein The covering layer includes at least one of a vinyl alcohol-based polymer and an alkylene glycol-based polymer.
5. The composite semipermeable membrane according to claim 4, wherein The vinyl alcohol polymer has a saponification degree of 96 mol% or more.
6. The composite semipermeable membrane according to claim 4, wherein The vinyl alcohol polymer has a degree of polymerization of 100 to 1,500.
7. The composite semipermeable membrane according to claim 4, wherein The vinyl alcohol polymer is a vinyl alcohol copolymer having a structure represented by the following general formula (1): [Chemical Formula 1] In the general formula (1), X is a divalent hydrocarbon group having 2 to 6 carbon atoms, and l, m, and n are the numbers of repeating units.
8. The composite semipermeable membrane according to claim 7, wherein X in the general formula (1) is a divalent hydrocarbon group having 2 carbon atoms.
9. The composite semipermeable membrane according to claim 8, wherein X in the general formula (1) is 1,2-ethylene.
10. The composite semipermeable membrane according to claim 7, wherein The copolymerization ratio of the vinyl alcohol copolymer: n / (l+m+n) is 0.035 to 0.
16.
11. The composite semipermeable membrane according to claim 4, wherein The molecular weight of the alkylene glycol polymer is 500 to 500,000.
12. A composite semipermeable membrane module comprising the composite semipermeable membrane according to claim 1 or 2.
13. A fluid separation device comprising the composite semipermeable membrane module according to claim 12.
Citation Information
Patent Citations
Composite semipermeable membrane and method for manufacturing the same
JP2003200026A
Composite semipermeable membrane and method for producing composite semipermeable membrane
JP2019098329A
Air conditioning system
JP2023015305A
Composite semipermeable membrane
WO2014104241A1